2017
DOI: 10.1007/s00590-016-1894-4
|View full text |Cite
|
Sign up to set email alerts
|

Revision anterior cruciate ligament reconstruction with ipsi- or contralateral hamstring tendon grafts

Abstract: The use of contralateral hamstring tendon autografts for ACL revision surgery produced similar subjective and objective outcomes at 6-years follow-up compared to revision with ipsilateral hamstring tendon autografts. Patients undergoing revision surgery with contralateral autografts experienced a quicker return to sports compared to patients who underwent ipsilateral DGST revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Their negative pivot-shift prevalence was lower compared with about 10% in previous reports. 24,29,57 In addition, the rerupture rate was 1.2% in their multicenter study. In our study, 90.5% in group C showed a negative pivot shift, while 53.5% in group I had a negative pivot shift (P \ .001).…”
Section: Discussionmentioning
confidence: 96%
“…Their negative pivot-shift prevalence was lower compared with about 10% in previous reports. 24,29,57 In addition, the rerupture rate was 1.2% in their multicenter study. In our study, 90.5% in group C showed a negative pivot shift, while 53.5% in group I had a negative pivot shift (P \ .001).…”
Section: Discussionmentioning
confidence: 96%
“…One level I study was identified (3%) [41]. There was one level II prospective cohort study (3%) [50], 10 levels III (39%) [3, 27, 33, 38, 45, 52, 57, 61, 68, 69], and 16 level IV observational studies (55%) [1, 3–5, 13, 6, 14, 20, 21, 29, 34, 35, 43, 51, 52, 58, 68]. The methodological quality of non‐comparative studies scored 10.3 out of 16 points using the MINORS criteria (64% of maximum score).…”
Section: Resultsmentioning
confidence: 99%
“…One additional study was found by screening references. A total of 28 studies reporting on failure modes were ultimately included, including 24 cohort studies [1, 3–5, 13, 6, 14, 19–21, 29, 34, 38, 43, 45, 46, 51, 52, 57, 58, 62, 63, 68, 69] and four registry‐based studies [33, 35, 50, 61]. Fourteen of the 24 cohort studies reported age at time of primary reconstruction [1, 3, 5, 13, 19, 21, 22, 29, 39, 43, 51, 52, 54, 58].…”
Section: Resultsmentioning
confidence: 99%
“…A contralateral autologous graft harvest for ACL revision could be advantageous in order to avoid further donor site morbidity in the injured limb. Studies on contralateral hamstring (HT) harvest for ACL revision report this as a feasible option [33], with a similar clinical and patient-reported outcome compared with both ipsilateral HT harvest and allograft [3436].…”
Section: Resultsmentioning
confidence: 99%